2015
DOI: 10.1074/jbc.m114.624809
|View full text |Cite
|
Sign up to set email alerts
|

Differential Ubiquitin Binding by the Acidic Loops of Ube2g1 and Ube2r1 Enzymes Distinguishes Their Lys-48-ubiquitylation Activities

Abstract: Background:The acidic loops of E2 enzymes are important for their Lys-48-ubiquitylation activity. Results: The presence of Tyr residues modulates the ubiquitin binding property of the acidic loop. Conclusion: A proper interaction of the acidic loop with the attached donor ubiquitin is important for Lys-48-ubiquitylation activity. Significance: One of molecular bases to study the mechanism of Lys-48-ubiquitylation is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…UBE2G1 and its paralog UBE2G2 share similar domain structures with CDC34. A common structural feature of these three E2 enzymes is an acidic loop (Figure S5A, highlighted with red) in the vicinity of their respective active site cysteines (Figure S5A, highlighted with blue), which facilitates the direct binding with ubiquitin and enables K48-linked ubiquitin chain assembly in the absence of associated E3 ligases (Choi et al, 2015). In association with gp78, an ER membrane bound RING finger E3 ubiquitin ligase, UBE2G2 directly tags misfolded proteins with K48-linked ubiquitin chains preassembled on the catalytic cysteine of UBE2G2, resulting in ER associated protein degradation (ERAD) (Li et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UBE2G1 and its paralog UBE2G2 share similar domain structures with CDC34. A common structural feature of these three E2 enzymes is an acidic loop (Figure S5A, highlighted with red) in the vicinity of their respective active site cysteines (Figure S5A, highlighted with blue), which facilitates the direct binding with ubiquitin and enables K48-linked ubiquitin chain assembly in the absence of associated E3 ligases (Choi et al, 2015). In association with gp78, an ER membrane bound RING finger E3 ubiquitin ligase, UBE2G2 directly tags misfolded proteins with K48-linked ubiquitin chains preassembled on the catalytic cysteine of UBE2G2, resulting in ER associated protein degradation (ERAD) (Li et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This orchestrated action between UBE2D3 and UBE2G1 closely resembles the cooperativity of UBE2D3 and Cdc34 in promoting IκBα polyubiquitination mediated by SCF βTRCP2 (Wu et al, 2010), except that unlike Cdc34, UBE2G1 does not possess the ability to transfer ubiquitin onto substrates without prior ubiquitin conjugation. UBE2G1 was known to produce K48-linked poly-ubiquitin chains in the absence of an E3 ubiquitin ligase (Choi et al, 2015), but UBE2G1 cannot promote GSPT1 ubiquitination in the absence of CC-885 or Cul4A-Rbx1 (Figure 4E), indicating that close proximity of UBE2G1 to cereblon neomorphic substrates bridged by CRL4 CRBN is required to increase the processivity of UBE2G1 at physiological concentrations. This provides an explanation to how cereblon modulating agents can induce effective substrate degradation via K48-linked polyubiquitination, as well as speaks to the potential role of UBE2G1 in mediating the ubiquitination and degradation of other CRL4 cognate and/or neomophic substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this well-known deciphering function of UBDs, the function of ubiquitin binding in polyubiquitin chain formation is poorly understood. For instance, the activities of the E2 enzymes Ubc13 (Pastushok et al, 2005), Ube2g1 (Choi et al, 2015), and Cdc34 (Choi et al, 2010) rely on ubiquitin binding events. In addition, it has already been shown that processive polyubiquitin chain formation can be promoted by noncovalent interactions of ubiquitin with the backside of certain E2 enzymes (Brzovic et al, 2006;Buetow et al, 2015) as well as by RING domains showing ubiquitin binding activity (Brown et al, 2014;Wright et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ube2R1/2 is a critical E2 that functions with the cullin-RING ubiquitin ligases (1,18), and, together, these enzymes may be responsible for 20% of all proteasome-dependent degradation in human cells (19). Ube2R1/2 contains an atypical insertion distal to its active site that contains several conserved acidic residues (20)(21)(22)(23)(24)(25), and this acidic loop has also been shown to have an important role in Lys 48 selectivity (26,27). More recent work has identified a loop on acceptor ubiquitin that contains residues that interact with the E2 in order to help place Lys 48 in the E2 active site (26).…”
mentioning
confidence: 99%